2017
DOI: 10.1002/qua.25370
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the redox properties of uranyl complexes using electronic structure calculations

Abstract: A plethora of chemical reactions is redox driven processes. The conversion of toxic and highly soluble U(VI) complexes to nontoxic and insoluble U(IV) form are carried out through proton coupled electron transfer by iron containing cytochromes and mineral surfaces such as machinawite. This redox process takes place through the formation of U(V) species which is unstable and immediately undergo the disproportionation reaction. Thus, theoretical methods are extremely useful to understand the reduction process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Among the five DFs, the M06 functional predicted a value of −1.56 V close to the experimental estimate of −1.54 V within 100 mV. We have earlier shown that the M06 functional predicts vertical and adiabatic detachment energies of uranyl complexes in close agreement with electron spray ionization photoelectron spectroscopic techniques . All other four functionals underestimate the redox potential by more than 500 mV.…”
Section: Experimental Sectionsupporting
confidence: 64%
“…Among the five DFs, the M06 functional predicted a value of −1.56 V close to the experimental estimate of −1.54 V within 100 mV. We have earlier shown that the M06 functional predicts vertical and adiabatic detachment energies of uranyl complexes in close agreement with electron spray ionization photoelectron spectroscopic techniques . All other four functionals underestimate the redox potential by more than 500 mV.…”
Section: Experimental Sectionsupporting
confidence: 64%
“…Grimme showed that the B3LYP density functional can be systematically improved through geometrical counterpoise correction . Much effort has been spent to develop new functionals, and recently, several highly optimized density functionals have been developed and many have been conceived specifically with transition metals in mind. Nonetheless, transition metals continue to challenge quantum chemical methods. For example, the performance of the new generation density functionals developed by Head-Gordon should be assessed in future studies, as they show very promising behavior and impressively small errors for a variety of properties such as thermochemistry, vibrational frequencies, and barrier heights.…”
Section: Challenges Of In-silico Catalyst Designmentioning
confidence: 99%
“…At the dawn of the 21st century, the redox chemistry of organoactinide complexes has experienced a remarkable revival and growth both experimentally and theoretically. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Indeed, in addition to the usual ligands such as chloride, carbocyclic ligands (C 5 R 5 , C 7 H 7 , C 8 H 8 ) and amides NR 2 , the use of a wider range of functionalized groups have led to high oxidation states actinide compounds (> +3) exploiting the stabilization induced by metal-ligand multiple bonds. 17,18 Furthermore, contrarily to the 4f lanthanide electrons which are essentially core electrons, 19 the 5f actinide electrons are involved in the bonding.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Moreover, the investigation of new ligands that could provide thermodynamic stabilization to high-valent uranium species, is interesting first on a fundamental point of view, but also to elaborate new separation techniques and storage methods and for the processing of nuclear wastes from the nuclear plants. 4,8,13,22,23 Indeed, uranium complexes are able to access several oxidation states ranging from U II to U VI . 24,25 Their redox properties and the availability of valence 5f/6d-orbitals to interact make uranium complexes remarkably suitable for exploring new catalytic reactions especially for small molecule activation chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation